Group Dynamics Among Beef Cattle Farmers in Merak Hamlet, Sumberwaru Village, Situbondo Regency - Dede Aprylasari; Siti Azizah; Titanio Auditya Pribadi (Agriwar Journal, 2024)
This research aims to get an overview of group dynamics, measure dynamism, and find out the relationship between livestock group dynamism and the level of ability to carry out beef cattle farming activities. This research was conducted in Merak Hamlet, Sumberwaru Village, Situbondo Regency, from February to April 2024. The population in this study was all members of the livestock group, totaling 24 people. Took Respondents from all group members who participated in grazing their livestock. Regarding data collection, researchers used observation, interviews, and documentation methods. The data was collected and analyzed using descriptive analysis; the second analysis is the dynamic category, and the third is the Spearman Rank correlation analysis. The results of the research show that 1) in one year one adult female cow produces one calf, each member of the group has 4-11 cows, the total number of cattle in Merak Hamlet is 1,442 heads; 2) The dynamism of the cattle farming business is based on goals, structure, function, guidance, cohesiveness, atmosphere, effectiveness, pressure and hidden intentions, on average farmer breeders are satisfied with an average score of 3.916 (78.33%) with a distribution of 22 people (92%), while farmer breeders opinion is quite satisfied as much as 0.08 (8.33%); 3) The relationship between group dynamism and the ability to carry out cattle farming business in livestock groups in Merak Hamlet is of opinion that they are satisfied with an average score of 4.08 (81.66%), while based on The results of the Sperm Rank analysis of dynamic relationships including age have a real relationship to group dynamics where the value of R is more significant than R. Meanwhile, the relationship between ability including age has a real relationship where the value of Rstable is greater than Rstable: age (0.723>0.409), formal education (0.689>0.409), non-formal (0.789>0.409), experience (0.690>0.409).